Investigating the Geotechnical Properties of the Lunar South Pole with NASA VIPER’s Mobility System - Erin Rezich; Valentin T. Bickel; Parker L. Francis; Arno Rogg; Antoine Tardy; Colin Creager; Heather A. Oravec; Alexander Schepelmann; Kimberly Ennico-Smith; Ariel Deutsch; Masatoshi Hirabayashi (The Planetary Science Journal, 2025)
The NASA Volatiles Investigating Polar Exploration Rover (VIPER) is capable of assessing the geotechnical properties of the lunar south pole’s terrain, specifically as they pertain to terramechanics or the wheel–terrain interaction, combining the rover’s mobility system and science payloads. This paper focuses on one key aspect of VIPER’s mission: the quantitative evaluation of geotechnical parameters via tractive performance by analyzing wheel and wheel–regolith interaction dynamics. As VIPER navigates the largely uncharted terrain of the Moon’s south pole, sophisticated onboard instrumentation will monitor and record detailed interactions between the rover’s wheels, chassis, and the lunar surface. These measurements will capture critical data such as wheel slip and sinkage, offering insights into the mechanical behavior of the soil under actual lunar conditions. The findings from VIPER are expected to provide a foundational understanding of the lunar south pole’s regolith mechanics, directly informing the design and navigation strategies of future lunar missions, including the deployment of more advanced rovers and crewed vehicles. By integrating lunar surface observations with the rover’s kinematic model and understood terrestrial mobility performance, the study aims to enhance predictive accuracy regarding rover tractive performance over sloped, level, and potentially volatile-rich terrain. Ground truth geotechnical assessments and proceeding mobility characterization work will serve as a cornerstone for verifying and improving both terrestrial test approaches and simulation models that underpin mission planning and risk management for subsequent explorations.